EFFECTS OF ZEOLITES ON LITTER FLOOR ON PERFORMENT OF BROILER - Dede Kardaya; Niken Ulupi (Institut Teknologi Bandung, 2006)
Effect of zeolites-spread litters on broiler performances under different floor spaces had been performed in five weeks. As many as 324 chicks of a day-old Hubbard strain were fed rations contained 3,000